Assessment of Stress Level and Quality of Life in Spinal Cord Injury Patients - Rizwana Yasmin, Samina Kousar, Saima Sultana, Nazi Noor, Jauhar Amin, Salma Iftikhar Abbasi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Spinal cord injury (SCI) involves severe physical, social, and also psychological consequences, and cause severe disturbance in normal daily activities of a person. Aim: To assess the stress level and quality of life (QOL) variation among spinal cord injured individuals. Study design: Descriptive Cross sectional. Methodology: Simple random sampling recruited 165 participants (15-75 years) both genders, from government and public hospitals of Lahore and Islamabad. Data was collected by using The “Perceived Stress Scale (PSS-14 item)”and “WHOQOL-BREF” (26-item). Data SPSS v.24 analyzed the data. Quantitative data was expressed in terms of frequency and percentages. Results were shown in tabular and graph forms. Results: On PSS questionnaires 87.9% experience moderate stress, 12.1% experience severe stress. On WHOQOL-Bref the average score of physical health was 53.18, psychological health was 55.42, social relationship was 69.16 and the lowest most score among four domains was environmental health 52.73. Practical Impact: This study provided information regarding the perceived level of stress and QOL in SCI patients that is the most ignorant portion of our society and recognized the importance of assessing variation of stress and QOL in these patients so health care team take appropriate decisions for the improvement of the health status of these client. Conclusion: It was concluded that SCI patients had moderate stress level and face life threatening complication associated with this injury. Thus, both physical disability and psychological disturbance may adversely impact their stress level and quality of life. Keywords: Stress, Quality of life, Spinal cord injury and Psychological Impact.